Nuances transmasculinas: um olhar junguiano - Santos, Ana Claudia Oliveira dos (2024)
This study investigated the perception of gender identity by transmasculine individuals and trans men who participated in a dream experience group. Culturally associated gender characteristics may become obstacles to the validation of non-binary transmasculinities, leading to processes of invisibilization and pressures for normative conformity. The lack of representation and understanding of diverse transmasculine expressions in society can contribute to these difficulties. The dream experience group provided a safe container space for symbolic and creative exploration of issues surrounding transmasculinities, as well as a supportive environment where participants could express their emotions. We observed that some of the participants, during their gender affirmation journey, have identified with a persona that reproduces binary patterns of masculinity. However, this quest for self-determination seems to be permeated by experiences that lead them on a journey of resignifications, through which it is possible to find a more authentic (trans)masculinity that expresses their own individuality. This research highlights the importance of building a more accessible and respectful clinic practice that values the subject's discourse and recognizes the diversity of transmasculine gender identities